1981
DOI: 10.1021/ma50004a003
|View full text |Cite
|
Sign up to set email alerts
|

Cationic copolymers of isobutylene. 5. Copolymerization of isobutylene and cis-1,3-pentadiene

Abstract: The structure of cationic isobutylene (I)-c¿s-l,3-pentadiene (cP) copolymer was investigated by means of 13C NMR spectroscopy. The diene was present in the copolymer chains mainly as trans-1,4 units, but cis-1,2, trans-1,2, trans-4,1, and trans-4,3 units were also observed. The attack at position 4 of cP occurred by sterically unhindered carbenium ions arising from cP and not from I. The isomerization of cP to irons-1,3-pentadiene was ascertained to occur under mild conditions in the presence of BFg-OEtg. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Unsaturation of PPD‐1, calculated through the comparison of intensities of protons or carbon atoms in olefinic and aliphatic regions of 1 H and 13 C NMR spectra, (a) were 89 and 91%, respectively. It should be noted that these values of unsaturation are the ones of the highest for PPDs synthesized by cationic polymerization . Owing to the low content of saturated structures in PPD‐1 sample, their structure is not investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Unsaturation of PPD‐1, calculated through the comparison of intensities of protons or carbon atoms in olefinic and aliphatic regions of 1 H and 13 C NMR spectra, (a) were 89 and 91%, respectively. It should be noted that these values of unsaturation are the ones of the highest for PPDs synthesized by cationic polymerization . Owing to the low content of saturated structures in PPD‐1 sample, their structure is not investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the absence of signal of methyl carbon atom of 3,4‐unit at 9–12 ppm in 13 C NMR spectrum indicates that PPD‐1 sample does not contain this structural unit. According to Rozentsvet et al, the signal 25 at 114.8–115.5 ppm (CH 2 group), which was misleadingly assigned to the structural fragment of 3,4‐unit, is in fact belonged to terminal groups of PPD chain, the exact structure of which is not identified up to date.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there have been some reports about the cationic copolymer of PD with other monomers, such as olefin, styrene [4][5][6][7][8][9][10][11], research in the cationic copolymerization of PD with AP has rarely been reported. We are interested in the cationic PD-AP copolymerization because it is of significance for synthesis of the copolymer with high softening point and light color.…”
Section: Introductionmentioning
confidence: 99%